Endgame? - Jakubowicz, Karol (Javnost (Ljubljana), 2003)
Public service broadcasting (PSB) in its traditional form is the product of a long gone era. Social, technological, ideological and cultural change has altered the entire context within which public broadcasting operates. Also media policy has evolved, moving beyond its "public service" phase to a new paradigm, devoted primarily to economic goals. With these changes, attitudes to PSB are changing, too. It is increasingly treated as an exception to the "normal" market-based rules governing broadcasting, indeed an anomaly. In thispaper we will seek to ascertain the effects of these changed attitudes, especially in terms of efforts to develop a precise definition of public broadcasting, and of evolution from "autonomy" to a "controlled public service" model of PSB. This involves a multitude of accountability systems, designed to ensure that PSB remains true to its remit and performs the service it was created to deliver. Defining public service broadcasting is notoriously difficult, all the more so that at least 9 models appear in European debates. Also developing accountability systems for PSB is far from easy because of the many contradictory views of the "product" that PSB is expected to "deliver." The question of auditing is part of a much wider debateon what public broadcasting needs to do to become more relevant to society today and how it needs to safeguard its own future. The main problem, however, is that imposition of "box-ticking" accountability systems based on outdated concepts to an institution in the midst of redefining itself could stop its modernization and thwart its ability to find a new identity in a much-changed context.
Keywords: množični mediji; radio; mass media; television; televizija; medijska politika; medijski trg; konkurenca